Modular organization of the head retraction responses elicited by electrical painful stimulation of the facial skin in humans. Issue 12 (December 2015) - Serrao, Mariano; Cortese, Francesca; Andersen, Ole Kæseler; Conte, Carmela; Spaich, Erika G.; Fragiotta, Gaia; Ranavolo, Alberto; Coppola, Gianluca; Perrotta, Armando; Pierelli, Francesco
Highlights: We found a well-defined modular organization of the head retraction reflexes (HRRs). HRR are related to withdrawal strategies aimed at protecting the face. Central nervous system may exploit trigeminocervical reflexes synergies to simplify head and neck motor control. Abstract: Objective: To explore whether the trigeminocervical reflexes (TCRs) show a reflex receptive field organization in the brainstem. Methods: The facial skin of 16 healthy subjects was electrically stimulated at nine sites reflecting the distribution of the three branches of the trigeminal nerve. The reflex-evoked EMG responses were measured bilaterally from the neck muscles and the head and neck kinematic reactions were detected. Results: TCRs are site dependent. There was a vertical gradient in the magnitude of the reflex responses. EMG and kinematic reflexes were larger when evoked from ophthalmic and maxillary sites than from mandibular ones. The reflex responses exhibited a crossed right–left behavior. Stimulation of the lateral sites evoked larger reflex responses in the contralateral trapezium muscle as well as head rotation and neck bending away from the stimulated side. Conclusion: This modular arrangement of the TCRs seems to be related to withdrawal strategies aimed at protecting the face from injuries, in accordance with the functional role that each group of muscles plays in head and neck motion. Significance: It is likely that the CNS may exploit the neck muscle synergies revealed by the painful stimulation of the skin face in order to control the head and neck movements.